Characterization of Japanese Polished Rice by Stable Hydrogen Isotope Analysis of Total Fatty Acids for Tracing Regional Origin - SUZUKI, Yaeko; AKAMATSU, Fumikazu; NAKASHITA, Rumiko; KORENAGA, Takashi (Analytical Sciences, 2013)
We determined the δD values of the total fatty acids of Japanese rice to test the hypothesis that there is a wide variation in the hydrogen isotopic composition (δD) of the total fatty acids of Japanese rice sourced from different growth areas in Japan and to distinguish the minor differences among these growth areas. The δD values showed a wide variation ranging from –216‰ (Hokkaido) to –183‰ (Okinawa), indicating a good correlation with the corresponding variations for ambient water (r = 0.63) and mean temperature (r = 0.84). These results suggest that the δD values for the total fatty acids can be representative of the growth environments in Japan.